(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
The process of protecting the accessibility, reliability, and secrecy of information is called Information security. We see a great increase in accessing of computer databases for stored information. Increasing number of companies are storing individual and business information on computers. Most of this information is not meant for the public eyes and is very sensitive. The following paper discusses the development of a block cipher based cryptographic algorithm that uses the logical gates like XOR and other shifting operations. The results of the experiment prove the algorithm to be efficient and secure.